Innovative tendencies in formation of the singers’ culture of the future specialists who represent artisric professions - Соболева, О. Д.; Цехмістро, О. В.; Дубовська, О. Л. (Scientific notes of the pedagogical department, 2017)
Оf vocal–choral teacher training In the article there is an analysis of innovative tendencies in formation the singers’ culture of the future specialists who represent artistic professions. The article also includes main approaches and methods that deal with vocal training with the usage of authorial unconventional methodologies. We have also examined a concept of vocal psychotechnics as the modern course of educational work with voice in higher educational establishments. The need for scientific substantiation content of vocal studies at the university, an integrated system of full training in the field of vocal art belongs to the urgent problems of modern musical culture and concerns the development of systematic and methodical complex vocal education in general. Current trends vocal training future professionals aimed at improving the content of vocal studies at universities and the creation of a systematic approach to the educational process, including developing holistic system–methodical complex. Psychotechnique direction to the vocal apparatus singer as «a living musical instrument» is one of the most difficult problems of modern vocal pedagogy because it is caused solely functional features of human intellectual activity that should provide a consistent and systematic process of mastering all aspects of phonation – from basic knowledge, skills, to the heights of vocal skills.Thus, the formation of a new approach to vocal and technical problems that have settled based on the functionality of IP rights is essential in the education of future professionals of artistic disciplines. Singing as a process, of course, refers to the purposeful actions that such manifestations of physical activity a singer that he understood and may change at its discretion. So, to keep singing and singers learn the secrets of technology is possible only if a conscious approach to learning and understanding the whole complex of the singers. It is this aspect of scientific knowledge can provide intelligent knowledge base and skills of the biophysical and physiological knowledge of vocal activity, in the center of which is a voice device, not as a system of rights, which is to form the sounds of voice and speech, and above all – singers «instrument», which is itself a singer and as an integrated structure micro particle macrocosm. The stated problems is promising for future research on finding innovative approaches and methods that should improve vocal pedagogy broader arsenal of tools to meet the requirements of time.